Enterprise JavaBeans 3.0 - Burke, Bill (Computer software developer) (O'Reilly, 2006)
If you're up on the latest Java technologies, then you know that Enterprise JavaBeans (EJB) 3.0 is the hottest news in Java this year. In fact, EJB 3.0 is being hailed as the new standard of server-side business logic programming. And O'Reilly's award-winning book on EJB has been refreshed just in time to capitalize on the technology's latest rise in popularity. This fifth edition, written by Bill Burke and Richard Monson-Haefel, has been updated to capture the very latest need-to-know Java technologies in the same award-winning fashion that drove the success of the previous four strong-selling.